A Selaginella lepidophylla Trehalose-6-Phosphate Synthase Complements Growth and Stress-Tolerance Defects in a Yeast tps1 Mutant - Zentella, Rodolfo (American Society of Plant Physiologists, 1999)
The accumulation of the disaccharide trehalose in anhydrobiotic organisms allows them to survive severe environmental stress. A plant cDNA, SlTPS1, encoding a 109-kD protein, was isolated from the resurrection plant Selaginella lepidophylla, which accumulates high levels of trehalose. Protein-sequence comparison showed that SlTPS1 shares high similarity to trehalose-6-phosphate synthase genes from prokaryotes and eukaryotes. SlTPS1 mRNA was constitutively expressed in S. lepidophylla. DNA gel-blot analysis indicated that SlTPS1 is present as a single-copy gene. Transformation of a Saccharomyces cerevisiae tps1Δ mutant disrupted in the ScTPS1 gene with S. lepidophylla SlTPS1 restored growth on fermentable sugars and the synthesis of trehalose at high levels. Moreover, the SlTPS1 gene introduced into the tps1Δ mutant was able to complement both deficiencies: sensitivity to sublethal heat treatment at 39°C and induced thermotolerance at 50°C. The osmosensitive phenotype of the yeast tps1Δ mutant grown in NaCl and sorbitol was also restored by the SlTPS1 gene. Thus, SlTPS1 protein is a functional plant homolog capable of sustaining trehalose biosynthesis and could play a major role in stress tolerance in S. lepidophylla.